2016
DOI: 10.11604/pamj.2016.24.257.9889
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between maternal pelvis height and other anthropometric measurements in a multisite cohort of Ugandan mothers

Abstract: IntroductionIn sub Saharan Africa, childbirth remains a challenge that creates the need for additional screening tools. Maternal pelvis height, which is currently in use by automotive engineers has previously been shown to have significant associations with various childbirth related outcomes and events. This study set out to determine the associations between maternal: Age, height, weight and number of pregnancies with maternal pelvis height in Ugandan mothers.MethodsThis was a secondary analysis of maternal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
(24 reference statements)
0
2
1
Order By: Relevance
“…For this analysis maternal tribe was used a proxy of the mothers genetic variability, thus the observed absence of the effect on site with inclusion of the tribe ICCs. This holds true despite our earlier observed mild effect of maternal tribe on the associations between maternal pelvis height and maternal height (Munabi et al, 2016a). This absence of effect on the duration of childbirth due to tribe is also supported by observations made in previous studies looking at immigrant populations in the United Kingdom (UK) found no difference in duration of childbirth for Chinese (Shah et al, 2011), Somali (Yoong et al, 2005), and Turks (Kanthasamy et al, 2013) compared with native white British women.…”
Section: Discussioncontrasting
confidence: 76%
“…For this analysis maternal tribe was used a proxy of the mothers genetic variability, thus the observed absence of the effect on site with inclusion of the tribe ICCs. This holds true despite our earlier observed mild effect of maternal tribe on the associations between maternal pelvis height and maternal height (Munabi et al, 2016a). This absence of effect on the duration of childbirth due to tribe is also supported by observations made in previous studies looking at immigrant populations in the United Kingdom (UK) found no difference in duration of childbirth for Chinese (Shah et al, 2011), Somali (Yoong et al, 2005), and Turks (Kanthasamy et al, 2013) compared with native white British women.…”
Section: Discussioncontrasting
confidence: 76%
“…African women are believed to have a more narrow pelvis than Europeans, which predisposes them to cephalopelvic disproportion [18,19]. Within Uganda, the mean pelvic height is significantly different within several tribes, yet regression modelling does not show a strong correlation between tribe and pelvic height [20]. The correlation between certain areas and pelvic height is stronger, which suggests that not so much the genetics of a certain tribe, but more so other determinants linked to a certain area that influence the pelvic size [20].…”
Section: Race and Tribementioning
confidence: 99%
“…It is assumed that these combined factors resulted in the current findings. The pelvic height and placenta are known to be larger in postpartum women than in primiparous women [ 42 , 43 ]. These may make later-borns less restricted in their growth in utero due to fewer structural restrictions and a more adequate supply of oxygen and nutrients [ 44 ].…”
Section: Discussionmentioning
confidence: 99%